Risk Modeling in Quality Assessment of Ready-Mix Concrete Using Simulation Methods - SKRZYPCZAK Izabela; ZIĘBA Joanna; PYTLOWANY Tomasz (Architecture, Civil Engineering, Environment)
Uncertainties associated with assessing the strength of concrete and the shortcomings of statistical criteria for assessing compliance are the reasons for formulating new procedures for classifying manufactured concrete, as well as for estimating risk when assessing its quality. Using the proposed model based on simulation methods and Gauss or Clayton copulas, it is possible to calculate the value of risk in the production of ready-mixed concrete with underestimated quality. Exposure to risk in assessing the quality of concrete can be measured as the product of the level of risk and the consequences of embedding under-quality concrete in a structure, and the developed matrix makes it possible to determine the level of risk and contribute not only to its quantification during the various phases of its production, but can affect the final quality of the concrete produced. Using the proposed model, the article calculates the level of risk in the production of ready-mixed concrete with underperformance.